Family and Career: An Analysis across Europe and North America - Luis Guirola; Laura Hospido; Andrea Weber (Institute of Labor Economics (IZA), 2024)
Using data on 17 countries in Europe and North America, we compare the career trajectories of mothers and fathers and of women and men without children across cohorts, and at different points of their life cycle. There is wide variation across countries in employment and earnings gaps at age 30. At age 50, however, employment between mothers and non-mothers have closed in most countries. We also observe convergence in employment gaps between mothers and fathers by age 50, but these gaps do not fully close. Motherhood gaps in earnings also close by age 50 between mothers and non-mothers, particularly among the highly educated. But there is strong persistence in earnings gaps between mothers and fathers even among highly educated parents. The main reasons for the remaining gaps at later stages in the life-cycle are part-time work among women and fatherhood premia as fathers' earnings outperform non-fathers' over their life-cycle.
Keywords: J12; J13; J16; J21; J22; 330; gender gaps; employment; earnings; children